Visit report of anemia in pregnancy case with blood type ab+ through a family medicine approach - Tamara Muliani; Margaretha Pramesthi Utari; Ella Windasari Gultom; Silviana Tirtasari (Institute of Computer Science (IOCS), 2023)
One of the direct causes of maternal mortality is anemia in pregnant women. In 2020, 36.5% of pregnant women suffered from anemia, and a 50% reduction is targeted for anemia in women of reproductive age in 2025. The incidence of anemia in pregnant women at Tangerang Regency in 2020 was 9,652 people. In the working area of the Cikupa Public Health Center, there was an increase in the rate of anemia in pregnant women. One of the cases is when Mrs. SH's increased Hb level becomes > 11 mg/dL and knowing the risk of anemia. Mrs. SH, 32 years old, came to the Cikupa Health Center G3P2A0 with a gestational age of 23 weeks. Laboratory results of hemoglobin 9.9 g/dL and blood group AB+. The patient had an anemic pregnancy for the first time and was a high-risk pregnancy due to a history of cesarean section, obesity, and the possibility of a transverse fetus. After the intervention, the patient's Hb level increased to 11.3 g/dL, the cause of anemia in Ny. SH is the patient's nutritional intake that did not vary, and she is lazy to control her pregnancy. The risk factors for Mrs. SH experienced anemia due to a lack of nutritious food intake, especially foods containing much iron, and not routine pregnancy control due to lack of attention in the third pregnancy. After the intervention, Mrs. SH increased to 11.3 g/dL.